Hepatitis B Virus Reactivation in Patients Receiving Interferon-Free Direct-Acting Antiviral Agents for Chronic Hepatitis C Virus Infection. (11th February 2017) - Liu, Chen-Hua; Liu, Chun-Jen; Su, Tung-Hung; Fang, Yu-Jen; Yang, Hung-Chih; Chen, Pei-Jer; Chen, Ding-Shinn; Kao, Jia-Horng
Abstract: Background: Little is known about the risk of hepatitis B virus (HBV) reactivation in patients receiving interferon (IFN)-free direct-acting antiviral agents (DAAs) for hepatitis C virus (HCV). Methods: Patients who were seropositive for HBV core antibody and who received IFN-free DAAs for HCV were enrolled. Hepatitis B virus reactivation was defined as reappearance of serum HBV deoxyribonucleic acid (DNA) ≥100 IU/mL in patients with baseline undetectable viral load, or ≥2 log10 IU/mL increase of HBV DNA in patients with baseline detectable viral load. Hepatitis B virus-related alanine aminotransferase (ALT) flare was defined as ALT ≥5 times upper limit of normal or ≥2 times of the baseline level. Hepatitis B virus-related hepatic decompensation was defined as presence of jaundice, coagulopathy, hepatic encephalopathy, or ascites. Results: Compared with no HBV reactivation in 81 HBV surface antigen (HBsAg)-negative patients, 2 of 12 HBsAg-positive patients had HBV reactivation (0% [confidence interval 95% CI, 0%–4.5%] vs 16.7% [95% CI, 4.7%–44.8%], P = .015). No patients had ALT flare or hepatic decompensation. Baseline HBsAg level at a cutoff value of 500 IU/mL was associated with HBV reactivation in HBsAg-positive patients. There was no HBsAg seroreversion in HBsAg-negative patients. Conclusions: Hepatitis B virus reactivation is limited to HBsAg-positive patients receiving IFN-free DAAs for HCV. Higher baseline HBsAg levels are associated with HBV reactivation. The risk of ALT flares or hepatic decompensation is low in these patients.